Manajemen Waktu : Strategi Untuk Kantor Yang Lebih Efisien - Fitrani Dwi Azzahra; Marsella Putri Tommy Amanda (Jurnal Manajemen Bisnis Era Digital, 2024)
Effective time management is a key factor in improving efficiency in an office environment. This article reviews various time management strategies and principles that can be applied in the office to increase productivity and create a balance between work and personal life. Retail company Yomart serves as a case study that demonstrates the implementation of best practices in time management, from the use of advanced technology to proper prioritization. Through these proactive measures, the company has managed to gain a deeper understanding of the importance of time management in achieving success and sustainability in a competitive market.